Juridical Analysis of Political Dynasty in Regional Head Elections in Indonesia - Juanda Yuviant Hafiidh; Moh. Indra Bangsawan; Jan Alizea Sybelle (Universitas Muhammadiyah Surakarta, 2023)
Political dynasty is a power run by a group of people who are still related by blood or within the family sphere. If we look at the reality of government in Indonesia, the practice of this power often occurs in political dynasties, one of which is in local government in Indonesia. The research method used by the author in this journal has a normative nature and is based on the perspective of democratic theory as a reference in writing this journal. Then, this type of research is descriptive qualitative with data analysis techniques in the form of literature studies by examining books and literature related to problems in this journal. A democratic state that involves the right of its people to participate in politics. Whereas autocratic states, political rights are granted and held to a larger group of citizens. Implicitly, it means that the phenomenon of political dynasties is a manifesto of an autocratic state. The phenomenon of political dynasties practiced by regional heads massively can be conceded that the practice of political dynasties has contradicted Article 7 letter r of the Election Law, but this article also contradicts the 1945 Constitution unconstitutionally and has no binding legal force.